Tolerogenic Dendritic Cells in Solid Organ Transplantation: Where Do We Stand? - Marín, Eros; Cuturi, Maria Cristina; Moreau, Aurélie (Frontiers in Immunology, 2018)
Over the last century, solid organ transplantation has been improved both at a surgical and postoperative level. However, despite the improvement in efficiency, safety and survival, we are still far from obtaining full acceptance of all kinds of allograft in the absence of concomitant treatments. Today, transplanted patients are treated with immunosuppressive drugs to minimize immunological response in order to prevent graft rejection. Nevertheless, the lack of specificity of immunosuppressive drugs leads to an increase in the risk of cancer and infections. At this point, cell therapies have been shown as a novel promising resource to minimize the use of immunosuppressive drugs in transplantation. The main strength of cell therapy is the opportunity to generate allograft-specific tolerance, promoting in this way long-term allograft survival. Among several other regulatory cell types, tolerogenic monocyte-derived dendritic cells (Tol-MoDC) appear to be an interesting candidate for cell therapy due to their ability to perform specific antigen-presentation and to polarize immune response to immunotolerance. In this review, we describe the characteristics and the mechanisms of action of both human Tol-MoDC and rodent tolerogenic bone marrow-derived dendritic cells (Tol-BMDC). Furthermore, studies performed in transplantation models in rodents and non-human primates corroborate the potential of Tol-BMDC for immunoregulation. In consequence, Tol-MoDC have been recently evaluated in sundry clinical trials in autoimmune diseases and shown to be safe. In addition to autoimmune diseases clinical trials, Tol-MoDC are currently used in the first phase I/II clinical trials in transplantation. Translation of Tol-MoDC to clinical application in transplantation will be also discussed in this review.